Histopathology of Kidney of Striped Catfish (Pangasiodon hypophthalmus) Feed with Turmeric Flour - Sri Wahyuni; Morina Riauwaty; Windarti Windarti (Jurnal Perikanan dan Kelautan, 2020)
Turmeric is an herbal plant that has antibacterial and antioxidant abilities, and also to improve the fish's immune system. The aim of this research was to look at the histological structure of kidney and survival rate fish which was given feed with turmeric flour before and after infected with A. hydrophila. This research was conducted from February to May 2019 in the Laboratory of Parasites and Fish Diseases of the Faculty of Fisheries and Marine Sciences, University of Riau. The method in this research was the experimental method by one-factor Completely Randomized Design (CRD) with five levels. Kn (feeding without given turmeric flour and without infection with A. hydrophila), Kp (Feeding without given turmeric flour and infected with A. hydrophila), P1 (turmeric flour at a dose of 0.5 g / kg of feed), P2 (dose of 0.7 g / kg), P3 (dose of 0.9 g / kg). The results showed that the histological structure of catfish which was given the addition of turmeric flour in feed by normal conditions and after being challenged with A. hydrophila showed some damage to the gill and kidney structure. The best dose of adding turmeric flour to feed is 0.7 g / kg of feed (P2), seen from the structure of the kidney cell, and the best survival. Histological structure of kidney cell structure in P2 treatment has abnormality such as hemorrhage and survival rate 100%.